THE EFFECT OF MYCORRHAZAL SUPPLY ON THE GROWTH AND YIELD OF CAYENNE PEPPER (Capsicum frutescens L.): THE EFFECT OF MYCORRHAZAL SUPPLY ON THE GROWTH AND YIELD OF CAYENNE PEPPER (Capsicum frutescens L.) - Ritaqwin, Zaitun (JOURNAL OF SOILSCAPE AND AGRICULTURE, 2026)
This study aims to observe the effect of administering AMF on the growth of chili plants and the level of root infection of chili plants. The research was conducted in May–September 2025 using a non-factorial Randomized Block Design (RBD) with one factor, namely the type of AMF consisting of four treatments: without (P0), (P1), (P2) and (P3) each treatment was given at a dose of 16 g of plants⁻1 and three replications. The parameters observed included plant height, number of leaves, number of fruits, and the percentage of root infection by mycorrhizae. The research data were analyzed using analysis of variance, followed by a DMRT test at the 5% level if significant effects were found. The results analysis showed that the application of AMF had no significant effect on the height of chili plants and the number of leaves at the ages of 15, 30, and 45 days after planting. However, descriptively, AMF treatment, especially mixed mycorrhiza treatment, showed a tendency to increase vegetative growth in the final growth phase. The number of chili pepper fruit did not differ significantly between treatments, although Glomus sp. inoculation resulted in the highest number of fruit compared to other treatments. The percentage of root infection increased with AMF application, indicated by the formation of hyphae, vesicles, and arbuscules, indicating the success of the mycorrhizal symbiosis with chili pepper roots. The results of the study showed that the administration of AMF has the potential to increase the physiological efficiency and nutrient uptake of chili plants, although the statistical effect is limited.